Inflation and incentives on labour-cost growth - Villalobos Céspedes, Daniel (2018)
The aim of this theoretical research is to formulate an econometric model to evaluate the influence of inflation rate and incentive wage rate on labor cost. For such purpose, some important assumptions are stated regarding this phenomenon in order to grasp a general understanding. The dynamics of labor cost depend on different circumstances, including economic conditions and private and public policies. Base salary, which could be the official minimum wage, is assumed to be given at each period of time (i.e. annually) and indexed upwards to inflation rate, while incentive is applied ex-post to base salary. The variation rate of employment or personnel hiring intervenes in the growth of labor cost based on base salary, workdays, and incentive.  Consequently, this model is comprised of six explicative variables of labor cost variation. It is concluded that inflation has a ladder effect, while incentive has a shadow effect on labor cost. Based on such variables, a theory is offered here regarding the effects of inflation and incentives in labor cost growth that would show labor capital participation and employment level. In addition, a hypothetical exercise is conducted in order to illustrate the explanatory power of the model.